Investigation of late-cycle soot oxidation using laser extinction and in-cylinder gas sampling at varying inlet oxygen concentrations in diesel engines. (1st April 2017) - Gallo, Yann; Malmborg, Vilhelm B.; Simonsson, Johan; Svensson, Erik; Shen, MengQin; Bengtsson, Per-Erik; Pagels, Joakim; Tunér, Martin; Garcia, Antonio; Andersson, Öivind
Highlights: Optical and in-cylinder sampling data show a slower soot oxidation when inlet oxygen is reduced. Reduced intake O2 lowers the maximum adiabatic flame temperature limiting OH production. The results point towards OH being the dominant oxidizer under diesel combustion. Abstract: This study focuses on the relative importance of O2 and OH as oxidizers of soot during the late cycle in diesel engines, where the soot oxidation is characterized in an optically accessible engine using laser extinction measurements. These are combined with in-cylinder gas sampling data from a single-cylinder engine fitted with a fast gas-sampling valve. Both measurements confirm that the in-cylinder soot oxidation slows down when the inlet concentration of O2 is reduced. A 38% decrease in intake O2 concentration reduces the soot oxidation rate by 83%, a non-linearity suggesting that O2 in itself is not the main soot oxidizing species. Chemical kinetics simulations of OH concentrations in the oxidation zone and estimates of the OH-soot oxidation rates point towards OH being the dominant oxidizer.